2008
DOI: 10.1111/j.1469-7580.2008.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of expression of Notch protein members in normal and pathological endometrium

Abstract: The objective of this study was to investigate the pattern of expression and the localization of Notch-1, Notch-4 and Jagged-1 in physiological and pathological human endometrium and to evaluate the expression levels of two major regulators of the G1 checkpoint, namely cyclin D1 and p21. Sixty samples of physiological endometrium and 60 samples of pathological endometrium were used for the study. Evaluation of the expression level and the distribution of Notch pathway members and cell-cycle proteins was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
3
45
1
1
Order By: Relevance
“…In oral squamous cell carcinoma, Notch-4 deregulation is implied to be related to the deregulation of developmental and differentiation pathways, as well as cell fate misspecification (17). Notch-4 also seems to be involved in the proliferation of human endometrium (18). The changes of Notch-4 expression level may induce the expression of two pro-angiogenic genes, NF-κB and MMP2, in cerebral endothelial cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…In oral squamous cell carcinoma, Notch-4 deregulation is implied to be related to the deregulation of developmental and differentiation pathways, as well as cell fate misspecification (17). Notch-4 also seems to be involved in the proliferation of human endometrium (18). The changes of Notch-4 expression level may induce the expression of two pro-angiogenic genes, NF-κB and MMP2, in cerebral endothelial cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Cobellis et al (2008) identified changes in the expression of Notch1, which was strongest during the mid-secretory phase, and Notch4, which was stronger during the proliferative phase. Conversely, Mitsuhashi et al (2012) more recently identified no differences in Notch1 and 3 across the cycle.…”
Section: Notch Signalling In the Endometriummentioning
confidence: 95%
“…Notch1 and 3 protein primarily localize to the glandular epithelium (Cobellis et al 2008, Mitsuhashi et al 2012, whereas Notch4 localizes primarily to the stroma (Cobellis et al 2008). In the only study to examine transcript, Notch1 and 3 expressions are higher in endometrial stromal cells compared with epithelium (Mikhailik et al 2009); however, this analysis was performed following isolation and culture and therefore may not represent in vivo expression.…”
Section: Notch Signalling In the Endometriummentioning
confidence: 97%
See 1 more Smart Citation
“…Todėl manoma, kad NOTCH1 ir JAG1 gali būti svarbūs ląstelių diferenciacijai, o NOTCH4 -proliferacijai. Vėžinėse ląstelėse nustatytas NOTCH1 baltymo raiškos padidėjimas bei NOTCH4 ir JAG1 baltymų raiškos sumažė-jimas (30). Kitų autorių duomenimis, NOTCH1, NOTCH3, DLL4 ir JAG1 baltymų kiekiai yra vienodi tiek sekretuojančiame, tiek proliferuojančiame sveikame endometriume, todėl jie nėra svarbūs ląstelių proliferacijai ir diferenciacijai.…”
Section: Notch Signalinio Kelio Vaidmuo Formuojantis Gimdos Kūno Vėžiuiunclassified